2019
DOI: 10.1097/aco.0000000000000787
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric ambulatory anesthesia: an update

Abstract: Purpose of review Ambulatory surgery is the standard for the majority of pediatric surgery in 2019 and adenotonsillectomy is the second most common ambulatory surgery in children so it is an apt paradigm. Preparing and managing these children as ambulatory patients requires a thorough understanding of the current literature. Recent findings The criteria for undertaking pediatric adenotonsillectomy on an ambulatory basis, fasting after clear fluids, post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 44 publications
0
10
0
4
Order By: Relevance
“…10 In our hospital, adenotonsillectomy accounts for 20% to 30% of overall operating room (OR) cases. We chose adenotonsillectomy to study the incidence and the treatment effectiveness of PONV because 1) it has been identified as an independent risk factor for PONV 6,11 ; 2) it is, usually, of a predictable length; 3) it warrants routine use of prophylactic agents for PONV; and 4) has had a previously standardized anesthesia protocol at our department. Therefore, longitudinal comparisons are feasible.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In our hospital, adenotonsillectomy accounts for 20% to 30% of overall operating room (OR) cases. We chose adenotonsillectomy to study the incidence and the treatment effectiveness of PONV because 1) it has been identified as an independent risk factor for PONV 6,11 ; 2) it is, usually, of a predictable length; 3) it warrants routine use of prophylactic agents for PONV; and 4) has had a previously standardized anesthesia protocol at our department. Therefore, longitudinal comparisons are feasible.…”
Section: Methodsmentioning
confidence: 99%
“…5 Otoplasty and adenotonsillectomy are among surgical procedures that are independent risk factors for PONV. 5,6 Great efforts have been made toward the prevention and treatment of PONV. The multimodal approaches including combination of multiple antiemetic drugs, aggressive fluid replacement, reduction of opioids, and volatile anesthetics have some successes of dealing with this very common problem.…”
Section: Introductionmentioning
confidence: 99%
“…Es bleibt aus dem Literaturstudium zu betonen, dass der wesentliche Erfolgsfaktor ambulanten Operierens in der kritischen Selektion der Fälle und der Antizipation von Komplikationen liegt [17,18,[21][22][23][24][25][26][27].…”
Section: Strukturelle Vorgabenunclassified
“…En USA se ha visto que un 4,8% de los niños (> 13 años) tienen un consumo persistente de opioides posterior a la cirugía, con riesgo de generar dependencia [8]. Por otro lado, se ha descrito mortalidad asociada a su uso en pacientes con trastornos obstructivos del sueño [9]. Considerando lo anterior, se han desarrollado protocolos ahorradores de opioides, donde una analgesia basada en AINES, dexmedetomidina, ketorolaco y bloqueos regionales proporcionan un manejo similar del dolor pero con menos EA y costos asociados [8].…”
Section: Dolor Posoperatorio En Cirugía Ambulatoria Pediátricaunclassified